Problems Facing Professionals Counselors in Public Secondary Schools in Nigeria and Way Forward - Amorha Ifeagachukwu; Bandekaji Chris Audu (Researchparks Publishing, 2021)
The roles of professional counselors in the development education cannot be underestimated especially in the public secondary schools. Counselors are employed to provide quality guidance and counseling services in schools. The assignment and responsibilities of counselors required a lot of human and materials resources to be able for them to discharge theirs functions. It is unfortunate that many counselors cannot effectively deliver their functions due to some challenges facing them. This paper intends to discuss the challenges facing counselors in public secondary schools in Nigeria. To do this, physical and online libraries were consulted for data. Both primary and secondary data were used to provide empirical support to the various points raised in the presentation. The data were sorted from print and online publication. The paper revealed that attending to large number of Students, inadequate infrastructural facilities, poor training and retraining, inadequate funding of guidance and counseling units, poor motivation, insecurity, lack of awareness of counselor’ responsibilities and lack of enough counselling period are the challenges facing counselors in public secondary schools in Nigeria. To address these challenges, the papers recommended that; more allocation should be given to the secondary schools and more funds should be allocated to the administration of guidance and counseling programme, more professional counselors should be employed and deployed to public secondary schools to reduce the high students-counselors ratio and government should ensure counseling offices and rooms are well equip and furnished with needed counseling facilities etc.